STRATEGI PENGEMBANGAN AGRIBISNIS ROSELA (Hibiscuss sabdariffa L) DI KABUPATEN TULUNGAGUNG - Risna Yunitasari; Sumarji Sumarji (Manajemen Agribisnis: Jurnal Agribisnis, 2020)
Rosella cultivation in East Java, especially in Tulungagung regency to date still have excellent opportunities and prospects. It is based on suitable climatic and soil conditions and is supported by the opening of both domestic and foreign markets. Nevertheless since its presence in 2012 until now the development of rosella agribusiness in Tulungagung regency tends to stagnate. For that we need a strategy to grow this business to give more positive impact felt among rosella farmers. The purpose of this study is to identify internal factors (strengths and weaknesses) and external (opportunities and threats) and formulate appropriate strategies in the development of rosella agribusiness in Tulungagung District. This research was conducted in some districts in Tulungagung Regency with the location determination done purposively. This type of research includes descriptive, quantitative and qualitative with purposive sampling technique. The respondents were 15 rosella farmers who had land above 150 m². This research was conducted for 5 months starting from January 2017 until June 2017. Primary data was obtained through observation, interview, questionnaire and documentation while secondary data from BPS Tulungagung, East Java BPS, Manpower Office and Agriculture Department of Tulungagung Regency. The data analysis technique used is SWOT. SWOT matrix quantitative data analysis shows that the most appropriate alternative strategy for the development of Rosella agribusiness in Tulungagung regency is by using the SO Strategy, with the highest score, that is 4.58 SO Strategy is a strategy that uses the power to exploit opportunities. Several SO strategy steps that can be done related to the development of rosella agribusiness in Tulungagung District are: a) to improve the quality and quantity of production by utilizing the aspect of easy cultivation and care of rosella plants, wide land, quality seeds and easy information access, b) Increase the variety of processed rosella in the form of food beverages as a product that has a competitive advantage through the high creativity of farmers, c) exploiting the exhibition and expo as a promotion event as well as information to the community that rosella is a prospective commodity and feasible to be developed